A Waveguide Gate‐Type Complex Detecting Mechanism on Micro‐Channel Plate Substrate. Issue 3 (1st May 2019) - Mu, Yining; Fan, Haibo; Liu, Chunyang; Liu, Guozhen
Abstract : The waveguide gate‐type mechanism on micro‐channel plate substrate was. rstly put forward for the complex photo detection in Free space optical communication (FSO). Based on the losses of energy coupling between both Micro‐channel plates (MCP), we further proposed waveguide gate‐type complex detecting mechanism, which was veri.ed in electron optic system by vacuum testing. With the application of the complex detecting mechanism, the device performance has greatly improved, including higher space optical transfer and wider dynamic detecting range.